Safety of 6′‐sialyllactose (6′‐SL) sodium salt produced by a derivative strain (Escherichia coli NEO6) of E. coli W (ATCC 9637) as a Novel Food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Alexandre Maciuk; Inge Mangelsdorf; Harry J McArdle; Androniki Naska; Carmen Pelaez; Kristina Pentieva; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on 6′‐sialyllactose (6′‐SL) sodium salt as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The NF is mainly composed of the human‐identical milk oligosaccharide (HiMO) 6′‐SL (sodium salt), but it also contains sialic acid, d‐glucose, d‐lactose, 6′‐sialyllactulose sodium salt, 3′‐sialyllactose (3′‐SL) sodium salt and a small fraction of other related saccharides. The NF is produced by fermentation by a genetically modified strain (Escherichia coli NEO6) of E. coli W (ATCC 9637). The information provided on the identity, manufacturing process, composition and specifications of the NF does not raise safety concerns. The applicant intends to add the NF to a variety of foods, including infant formula and follow‐on formula, food for special medical purposes and food supplements (FS). The target population is the general population. The applicant applies for the same uses and use levels already assessed for 6′‐SL sodium salt produced by fermentation by a genetically modified strain of E. coli K‐12 DH1. Therefore, since the NF would be consumed at the same extent as the already assessed 6′‐SL sodium salt, no new estimates of the intake have been carried out. Similarly, FS are not intended to be used if other foods with added 6′‐SL or human milk are consumed on the same day. The Panel concludes that the NF is safe under the proposed conditions of use.